Método Alkire-Foster: uma alicação para a medição da pobreza multidimensional no Rio Grande do Sul (2000-2010) - Vieira, Carine de Almeida (2016)
The concept of poverty has evolved from traditional analyzes, based on income, for analyzes that try to encompass the various dimensions of people's lives. Because of this, it has been made a several attempts to poverty measurement methods with several variables beyond monetary income. One of multidimensional methodology applied the IMP (Multidimensional Poverty Index) based on the Alkire-Foster method (2009). The main advantage of this method is the use of two cutting lines, and its decomposition in dimensions, indicators, regions, etc. This study aimed to apply this methodology to all municipalities from the state of Rio Grande do Sul between 2000 and 2010. The results indicate that between the years analyzed the multidimensional poverty, in general, has decreased in the state of Rio Grande do Sul. The most deprived are the indicators type of sewer sanitation facilities and years of study, there was a reduction in the percentage of deprivation between 2000 and 2010, but there is still a large portion of which is private. Except from literacy indicator, all indicators had declines in the percentage of deprivation. It was observed that there was a decrease of 0.59 percentage points in literate people from 9 years old between 2000 and 2010. The results indicated a decrease in the incidence of multidimensional poverty in Rio Grande do Sul from 24.16% to 14 71% of the sample. Likewise, there was a decrease in mean that multidimensionally poor indicators are deprived of 41.71% in 2000 to 37.67% of the indicators. The adjusted incidence in the state of Rio Grande do Sul fell from 10.71% in 2000 to 5.54% in 2010. It should be noted that the amplitude between the municipalities with the highest and lowest poverty incidence also had a fall in the years analyzed. Cities with lower poverty incidence in 2010 were Porto Alegre, Dois Irmãos, São Leopoldo, Esteio and Caxias do Sul. Municipalities with the highest poverty incidence in 2010 were Chuvisca, Barão do Triunfo, Jari, Barão Xavier and Capão Bonito Sul.